Effect of storage temperature in a Cambodian field setting on the fatty acid composition in whole blood. (May 2015) - Nurhasan, M.; Roos, N.; Aristizabal Henao, J.J.; Chamnan, C.; Stark, K.D.; Lauritzen, L.
Abstract: Fatty acid analysis requires standardized collection and storage of samples, which can be a challenge under field conditions. This study describes the effect of storage temperature on fatty acid composition in two sets of whole blood samples collected from 66 children in a rural area in Cambodia. The samples were stored with butylated hydroxytoluene at −20 °C and −80 °C and the latter required extra transfers due to storage facility limitation. Fatty acid composition was analyzed by high-throughput gas-chromatography and evaluated by paired t -tests and Bland–Altman plots. Total amounts of fat in −20 °C and −80 °C samples did not differ, but there was relatively more highly unsaturated fatty acids (15.8±2.7 vs. 14.4±2.5%, p <0.001) and a lower n-6/n-3 ratio (6.4±1.4 vs. 6.9±1.4, p <0.001) in the −20 °C samples. Our results indicate that the importance of storage temperature should be evaluated in the context of storage facility availability and risk of temperature fluctuations during transport.